Long thermal stability of inverted perovskite photovoltaics incorporating fullerene-based diffusion blocking layer - Galatopoulos, Fedros; Papadas, Ioannis T.; Armatas, Gerasimos S.; Choulis, Stelios A. (My University, 2018)
In this article, the stability of inverted (p-i-n) perovskite solar cells is studied under accelerated heat lifetime conditions (60 °C, 85 °C, and N2 atmosphere). By using a combination of buffer layer engineering, impedance spectroscopy, and other characterization techniques, the interaction of the perovskite active layer with the top Al metal electrode through diffusion mechanisms is proposed as the major thermal degradation pathway for planar inverted perovskite photovoltaics (PVs) under 85 °C heat conditions. It is shown that by using thick solution processed fullerene buffer layer the perovskite active layer can be isolated from the top metal electrode and improve the lifetime performance of the inverted perovskite photovoltaics at 85 °C. Finally, an optimized reliable solution processed inverted perovskite PV device using thick fullerene diffusion blocking layer with over 1000 h accelerated heat lifetime performance at 60 °C is presented.
Keywords: Accelerated heat lifetime; Electrodes; Fullerene blocking layers; Perovskites; Thermal stability